Commentary On The 40th Anniversary of AMERSA: AMERSA at 40: How It All Began And How It Survived. Issue 2 (3rd April 2018) - Lewis, David; Schnoll, Sidney H.
Abstract: The question at hand for the 40th anniversary of AMERSA is how an organization with such a small membership devoted to substance use disorder medical education actually survived for 40 years. There were many obstacles. AMERSA had limited resources and only modest outside support. It was surrounded by large addiction specialty medical organizations with large budgets, some with membership in the thousands. Further, the missions of these larger organizations included medical education. Our longevity can be ascribed to these four critical periods and events. The Career Teacher Program (1972-1981), The decision by AMERSA in 1983 to remain an independent national organization, The AMERSA standard setting conference of 1985, AMERSA's Strategic Plan for Interdisciplinary Faculty Development and Project Mainstream (1999-2003).